FDI, catch-up growth stages and stage-focused strategies - Terutomo Ozawa (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
For the initial stage of catch-up growth, the "FDI-led takeoff" is an expedient alternative to the traditional infant-industry protection approach. Higher stages call for more nuanced, national-interests-dictated strategies to enhance domestic knowledge capability. A stages perspective cannot be overemphasized.
Keywords: 330